Potential effect of dietary zinc intake on telomere length: A cross-sectional study of US adults - Shi, Huanchen; Li, Xiaoxuan; Yu, Haihong; Shi, Wanting; Lin, Yue; Zhou, Yunping (Frontiers in Nutrition, 2022)
Background: Telomere length, which is related to chronic diseases and premature mortality, is influenced by dietary factors. Zinc is known as a dietary antioxidant micronutrient, however, its impact on telomere length remains unclear. Objective: We aimed to examine the potential effect of dietary zinc intake on telomere length among middle-aged and older individuals in the US. Methods: Our study included 3793 US participants aged 45 years and older from the 1999 to 2002 National Health and Nutrition Examination Survey (NHANES). 24-hour dietary recall interviews were employed to evaluate zinc consumption. Leukocyte telomere length was assessed by real-time quantitative polymerase chain reaction (qPCR). We adopted generalized linear models to investigate the effect of dietary zinc intake on telomere length, and subgroup analyses were further applied. We further evaluated the dose-response relationship using restricted cubic spline analysis. Results: Among the 3793 participants, the average telomere length was 0.926±0.205 (T/S ratio) or 5509.5±494.9 (bp). After adjusting for major confounders, every 5 mg increment in dietary zinc consumption was related to 0.64% (95% CI: 0.17%, 1.10%) longer telomere length. In the subgroup analyses, significant relationships were found in females (Percentage change: 1.11%; 95% CI: 0.48%, 1.75%), obese (Percentage change: 0.88%; 95% CI: 0.26%, 1.50%) and low energy intake individuals (Percentage change: 0.99%; 95% CI: 0.51%, 1.46%). Additionally, we revealed a positive linear relationship between dietary zinc intake and telomere length (P for non-linearity=0.636). Conclusions: Our study revealed that elevated dietary zinc intake was significantly related to longer telomere length among adults aged 45 years and older in the US. And the association was more pronounced in females, obese and low energy intake individuals.